Atherosclerosis, vascular amyloidosis and brain hypoperfusion in the pathogenesis of sporadic Alzheimer's disease - Kalback, Walter (2004)
We postulate that severe atherosclerotic occlusion of the circle of Willis and leptomeningeal arteries is an important factor in the pathogenesis of some sporadic Alzheimer's disease (AD) cases. These arterial stenoses are complicated by an overwhelming amyloid accumulation in the walls of leptomeningeal and cortical arteries resulting in a significant decrease in perfusion pressure and consequent ischemia/hypoxia of the brain tissue. We also propose that the distal areas of the white matter (WM) will be the first affected by a lack of oxygen and nutrients. Our hypotheses are supported by the following observations: (1) the number of stenoses is more frequent in AD than in the control population (p = 0.008); (2) the average index of occlusion is greater in AD than in the control group (p < 0.00001); (3) the index of stenosis and the total number of stenoses per case are positively correlated (R = 0.67); (4) the index of stenosis correlates with the neuropathological lesions of AD and with the MMSE psychometric test; (5) the number and degree of atherosclerosis of the anterior, middle and posterior cerebral arteries is more severe in cases of AD than in the control population; (6) atherosclerosis severity is apparently associated with the severity of the vascular amyloidosis; (7) the WM rarefaction correlates with the severity of the atherosclerosis and vascular amyloidosis; (8) the total cell count and microvessel count in the areas of WM rarefaction correlate with the neuropathological lesions of AD and with the MMSE score. Our data strongly suggest that severe hemodynamic disturbances contribute to sporadic AD and support the numerous observations indicating cardiovascular system participation in the pathogenesis of these dementias.